Injectable cellulose-based hydrogels as nucleus pulposus replacements: Assessment of in vitro structural stability, ex vivo herniation risk, and in vivo biocompatibility. (August 2019) - Lin, Huizi Anna; Varma, Devika M.; Hom, Warren W.; Cruz, Michelle A.; Nasser, Philip R.; Phelps, Robert G.; Iatridis, James C.; Nicoll, Steven B.
Abstract: Current treatments for intervertebral disc degeneration and herniation are palliative only and cannot restore disc structure and function. Nucleus pulposus (NP) replacements are a promising strategy for restoring disc biomechanics and height loss. Cellulose-based hydrogel systems offer potential for NP replacement since they are stable, non-toxic, may be tuned to match NP material properties, and are conducive to cell or drug delivery. A crosslinked, carboxymethylcellulose-methylcellulose dual-polymer hydrogel was recently formulated as an injectable NP replacement that gelled in situ and restored disc height and compressive biomechanical properties. The objective of this study was to investigate the translational potential of this hydrogel system by examining the long-term structural stability in vitro, the herniation risk and fatigue bending endurance in a bovine motion segment model, and the in vivo biocompatibility in a rat subcutaneous pouch model. Results showed that the hydrogels maintained their structural integrity over a 12-week period. AF injury significantly increased herniation risk and reduced fatigue bending endurance in bovine motion segments. Samples repaired with cellulosic hydrogels demonstrated restored height and exhibited herniation risk and fatigue endurance comparable to samples that underwent the current standard treatment of nucleotomy. Lastly, injected hydrogels elicited a minimal foreign body response as determined by analysis of fibrous capsule development and macrophage presence over 12 weeks. Overall, this injectable cellulosic hydrogel system is a promising candidate as an NP substitute. Further assessment and optimization of this cellulosic hydrogel system in an in vivo intradiscal injury model may lead to an improved clinical solution for disc degeneration and herniation.